Conventional Mirror Therapy versus Immersive Virtual Reality Mirror Therapy: The Perceived Usability after Stroke - Eliana da Silva Jaques; Anelise Ineu Figueiredo; Aniuska Schiavo; Bianca Pacheco Loss; Gabriel Hoff da Silveira; Vicenzo Abichequer Sangalli; Denizar Alberto da Silva Melo; Léder Leal Xavier; Márcio Sarroglia Pinho; Régis Gemerasca Mestriner (Stroke Research and Treatment)
Background. Stroke is a widespread and complex health issue, with many survivors requiring long-term rehabilitation due to upper-limb impairment. This study is aimed at comparing the perceived usability of two feedback-based stroke therapies: conventional mirror therapy (MT) and immersive virtual reality mirror therapy (VR). Methods. The study involved 45 participants, divided into three groups: the stroke survivors (n=15), stroke-free older adults (n=15), and young controls (n=15). Participants performed two tasks using both MT and VR in a semirandom sequence. Usability instruments (SUS and NASA-TLX) were applied at the end of the activities, along with two experience-related questions. Results. The results indicated that both MT and VR had similar levels of perceived usability, with MT being more adaptable and causing less overall discomfort. Conversely, VR increased the perception of task difficulty and prevented participants from diverting their attention from the mirror-based feedback. Conclusion. While VR was found to be less comfortable than MT, both systems exhibited similar perceived usability. The comfort levels of the goggles may play a crucial role in determining the usability of VR for upper limb rehabilitation after stroke.